غالب اور اقبال کی شخصیت کا تقابل (سوانحی و عصری حالات کے تناظر میں ): COMPARISON OF THE PERSONALITIES OF GHALIB AND IQBAL (IN THE CONTEXT OF HISTORICAL AND CONTEMPORARY CIRCUMSTANCES) (Al-Aasar, 2026)
Personal and contemporary circumstances affect the personality of any individual. Ghalib and Iqbal are two such Urdu poets who were particularly influenced by their personal and contemporary circumstances, which can be estimated from the study of their poetry and prose. Keeping this aspect in mind, this article studies and compares the personalities of these two poets in the context of their biography and contemporary circumstances. Although the personal circumstances and environment of both poets are different from each other and both were brought up in different environments, the requirements of both times were also different, but despite all this, there is some commonality in the personalities of both, which has been clarified in the article under consideration. The strategies adopted by both of them to deal with the difficulties of life have also been discussed. In this regard, the similarities and differences between the personalities of Ghalib and Iqbal have been presented in this section.